Interference Removal with an Improved Incremental Estimation Filter - Kors, J. A. (Methods of Information in Medicine, 1994)
Mains interference in digitized electrocardiographic signals is often removed with a nonlinear filter, the so-called incremental estimaton filter. A prerequisite for proper functioning of the filter is that the variation of the signal is considerably slower than that of the disturbing interference. This condition will often not be true, especially during wave deflections. As a result, the filter will not fully remove the interference when present, or, alternatively, it may generate a sine wave in the absence of interference. These effects are analyzed and different solutions proposed, one of which is the use of new, very simple filters based on the incremental estimation technique.
Keywords: Mains Interference; Nonlinear Filter; Electrocardiogram